An unconstrained integral approximation of large sliding frictional contact between deformable solids. (June 2015) - Poulios, Konstantinos; Renard, Yves
Highlights: Inequality constraints converted to non-smooth equalities before discretization. Method resulting to very low fluctuations of friction forces in numerical examples. Reporting number of full Newton iterations for a series of well documented examples. Proposing the term "raytracing" for avoiding ambiguity between projection strategies. Abstract: A new integral approximation of frictional contact problems under large deformations is presented. Impenetrability, friction and the relevant complementarity conditions are expressed through a non-smooth equation, considered in the continuous setting. A weak formulation of this non-smooth complementarity equation is discretized through a standard Galerkin procedure, is linearized consistently and incorporated in a generalized Newton solution process. The resulting integral handling of contact and friction complementarity conditions, previously implemented for small deformations only, is extended in the present paper to large deformations. In total, the proposed method is relatively simple to implement, while its robustness is illustrated through numerical examples.